Formal aspects of derogation of human rights due to the pandemic of COVID 19 in comparative practice of constitutional courts - Beretka Katinka (Anali Pravnog Fakulteta u Beogradu)
The paper presents the similarities and differences in the argumentation of the constitutional courts of the Republic of Serbia, the Republic of Croatia, Bosnia and Herzegovina, and Hungary when deciding on procedural/formal aspects of human rights derogation and other (restrictive) measures adopted due to COVID-19, such as the competence of bodies ordering restrictive measures, character/quality of their acts, control by the legislature and/or the executive. The commonality is that, despite the courts not neglecting the need for restrictive measures and the general interest in preserving public health, they treated the importance of formal requirements of the rule of law differently in pandemic conditions. The aim of this paper is to identify relevant common criteria and tests for assessing the constitutionality of these measures, in order to increase legal certainty in similar situations in the future, caused by new epidemics.